GENERAL STRUCTURE OF CAR ENGINES - Xashimov Jamshid Abdukaxarovich (Web of Journals Publishing, 2025)
This article expresses thoughts on the general structure of car engines, their types, parts, tasks.
Keywords: car engines, slindr blocks, porches, shatuns, combustion, piston movement.